2017
DOI: 10.2147/copd.s138867
|View full text |Cite
|
Sign up to set email alerts
|

Self-management behaviors to reduce exacerbation impact in COPD patients: a Delphi study

Abstract: BackgroundLittle is known about which self-management behaviors have the highest potential to influence exacerbation impact in COPD patients. We aimed to reach expert consensus on the most relevant set of self-management behaviors that can be targeted and influenced to maximize reduction of exacerbation impact.Materials and methodsA 2-round Delphi study was performed using online surveys to rate the relevance and feasibility of predetermined self-management behaviors identified by literature and expert opinion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
(62 reference statements)
0
31
0
2
Order By: Relevance
“…Total scores, means and standard deviations (SDs) were calculated for all consensus-reaching barriers and facilitators and respondent-suggested techniques in order to ascertain the order of ranking as it was possible that some could have the same percentage of respondent consensus. This follows methods used in previous modified Delphi surveys ( Fisher et al, 2013 ; Gallagher, Bradshaw, & Nattress, 1996 ; Hagen et al, 2008 ; Korpershoek, Bruins Slot, Effing, Schuurmans, & Trappenburg, 2017 ). SPSS v24 was used for analysis carried out on all quantitative data.…”
Section: Methodsmentioning
confidence: 99%
“…Total scores, means and standard deviations (SDs) were calculated for all consensus-reaching barriers and facilitators and respondent-suggested techniques in order to ascertain the order of ranking as it was possible that some could have the same percentage of respondent consensus. This follows methods used in previous modified Delphi surveys ( Fisher et al, 2013 ; Gallagher, Bradshaw, & Nattress, 1996 ; Hagen et al, 2008 ; Korpershoek, Bruins Slot, Effing, Schuurmans, & Trappenburg, 2017 ). SPSS v24 was used for analysis carried out on all quantitative data.…”
Section: Methodsmentioning
confidence: 99%
“…However, a more detailed view on these aggregated results shows that still a substantial proportion of COPD patients barely benefits from these kind of interventions. This might be explained by the ‘one size fits all’ and static approach regarding design, intensity and mode of delivery, the sole focus on exacerbation detection and taking action and suboptimal use of interventions [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To further reduce the impact of exacerbations, a more comprehensive, dynamic and individualized strategy is needed that improves the full spectrum of exacerbation-related self-management behavior [ 11 , 14 , 15 ]. Since previous studies have shown that self-management interventions only improve patient outcomes when changing self-management behavior of COPD patients [ 16 , 17 ], it is important that COPD self-management interventions aim at motivating, engaging and supporting patients to positively adapt their behaviors [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 The Delphi method has been used to establish consensus across a range of subject areas, including in the field of public health and clinical trials. 14 , 15 In this study, a three-round Delphi process was used to identify risks that likely occur in clinical trials of CAR T-cell therapy that also have the potential to cause great harm to the safety of the subject ( Figure 1 ). Prior to the Delphi process, a brainstorming session and literature review were conducted to identify the core clinical trial processes that involved potential risks.…”
Section: Methodsmentioning
confidence: 99%